Psychosocial Treatment of an Adolescent in a Hospital-Based Violence Intervention Program - Matthew Krock; Kimberly Burkhart; Edward Barksdale (MDPI AG, 2023)
Interpersonal violence is the leading cause of death in adolescents. Hospital-based violence intervention programs (HVIPs) address the emotional and behavioral sequelae of assault and homicide. Few studies have been published on pediatric HVIPs, and no study offers a conceptualization model for treatment approaches. This paper demonstrates the use of empirically supported practices by outlining the services provided and subsequent treatment trajectory of an adolescent receiving care from an HVIP at a Level 1 Pediatric Trauma Center. This case study follows the Case Study Report (CARE) guidelines and is the first to demonstrate the use of intensive case management, Psychological First Aid (PFA), and Skills for Psychological Recovery (SPR) in the treatment of an adolescent presenting to the emergency department (ED) due to assault associated with bullying. Through the use of these treatment approaches to address symptoms of posttraumatic stress, the patient moved from physical recovery to posttraumatic growth. Assessment and trauma-informed treatment suggestions are provided to support evidence-based practices within HVIPs.